Assessing the strategic needs of local territorial systems (LTSs): The case of a southern Italian province. Issue 4 (7th June 2018) - Pino, Giovanni; Guido, Gianluigi; Peluso, Alessandro M.; Pichierri, Marco
Abstract : Purpose: This paper aims to contribute to the literature on place marketing by focusing on the concept of strategic needs, i.e. the set of strategic priorities that a place could achieve in a medium- to long-term horizon to improve its development. Design/methodology/approach: The research examines the strategic needs of four local territorial systems (LTSs), i.e. clusters of municipalities that share social, economic and spatial similarities, located in a southern Italian province, through an analysis of their competitive positioning over three temporal instants. Findings: For each LTS, the analysis identified a number of development goals that local policymakers could pursue and the strategies most suitable to achieve the said goals. Originality/value: This paper proposes a new methodological approach to set the development goals of local areas based on the simultaneous assessment of their attractiveness and competitive capacity.